Angiogenesis Research: Guidelines for Translation to Clinical Application - Folkman, Judah; Browder, Timothy; Palmblad, Jan (Thrombosis and Haemostasis, 2001)
Angiogenesis research is being translated to the clinic. Certain guidelines may facilitate this effort. Recruitment of endothelial cells by a tumor is an early event in angiogenesis, a process regulated at genetic and epigenetic levels. The microvascular endothelial cell has become an important second target in cancer therapy. Angiogenesis inhibitors are either “direct” or “indirect” and their optimal dosing depends on a different logic than conventional chemotherapy. Conversely, antiangiogenic scheduling of chemotherapy can by-pass drug resistance. Like all solid tumors, hematologic malignancies are angiogenesis-dependent. Further, angiogenesis is modulated by proteins and cells from the hematopoietic and hemostatic systems. Clinical testing of angiogenesis inhibitors has accentuated the need for surrogate markers of tumor angiogenesis activity. Microvessel density, so valuable as a prognostic indicator of metastatic risk, cannot determine efficacy of an angiogenesis inhibitor. In the future, angiogenesis inhibitors may be added to chemotherapy or to radiotherapy, or to other modalities. Also, combinations of angiogenesis inhibitors may be administered together.
Keywords: Angiogenesis; leukemia; antiangiogenic therapy; angiogenesis inhibitor